2008
DOI: 10.1016/j.ejvs.2008.08.017
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the Swedvasc Registry: A First-time Individual Cross-matching with the Unique Personal Identity Number

Abstract: The external and internal validity of the Swedvasc registry allows to confidently assess volumes of, and mortality after, vascular surgery in Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(105 citation statements)
references
References 22 publications
1
103
0
1
Order By: Relevance
“…Nonetheless, previous validation of the Swedvasc registry has shown excellent external and internal validity, 5 and data quality has been improved by merging the databases, which all use the same personal identity code to identify patients, as well as by reviewing individual case records. As has been commented on previously, not all patients gave their consent for retrospective review of medical records.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, previous validation of the Swedvasc registry has shown excellent external and internal validity, 5 and data quality has been improved by merging the databases, which all use the same personal identity code to identify patients, as well as by reviewing individual case records. As has been commented on previously, not all patients gave their consent for retrospective review of medical records.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 A detailed analysis of the stroke register data quality has shown that the concordance between hospital inpatient medical records versus data recorded in the stroke register is high (≥95%) for stroke subtype and clinical parameters. The vascular and stroke registries complement each other with regard to pre-, peri-, and postoperative data.…”
Section: Study Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The external validity of the registry is high and covers Ͼ93% of all CEAs performed in Sweden. 20 Because the data are prospectively gathered from a heterogeneous unselected population in everyday clinical practice, they are therefore well suited to monitor the effects of changes in guidelines on the timing of CEA. However, it is important to note that our study is not randomized and there may be differences between the subgroups that we did not identify.…”
Section: Discussionmentioning
confidence: 99%
“…These results have shown 93.7% to 100% completeness. 20,21 Several articles have also studied the external and internal validation of Swedvasc showing high accuracy regarding stroke and death within 30 days postoperatively. [22][23][24] We obtained data for patients who underwent intervention for symptomatic carotid stenosis in Sweden between May 12, 2008, and May 31, 2011, and were recorded in Swedvasc (nϭ2763).…”
Section: Study Populationmentioning
confidence: 99%